Which Adiposity Marker Is Most Strongly Associated with All‑Cause and Cause‑Specific Mortality? a Prospective Study of 158,699 Mexican Adults - De Moraes-Ferrari, G (Springer Nature, 2025)
Background: Various methods have been used to assess adiposity and its associations with morbidity and mortality. In this study, we aimed to examine the association of four adiposity markers with all‑cause and cause‑specific mortality, while evaluating the potential influence of reverse causation bias. Methods: This prospective cohort study included 158,699 participants from the Mexico City Prospective Study. Cox regression models were performed to estimate the associations of body mass index, waist circumference, waist-to-height ratio, and waist-to-hip ratio with mortality risk. To minimize the influence of reverse causation, we excluded participants with prevalent diseases at baseline and conducted additional analyses excluding deaths occurring within the first 2, 5, and 10 years of follow-up. Results: Over a median of 15.5 years, 28,296 death were recorded. Waist circumference values above the recommended cutoff considered high were associated with higher all-cause mortality after the exclusion of the first 2, 5, and 10 years of follow-up (HR: 1.83; 95% CI: 1.26–2.55, HR: 1.83; 95% CI: 1.23–2.62, and HR: 1.85; 95% CI: 1.14–2.70, respectively). Elevated waist-to-hip ratio was associated with increased all-cause mortality across the same exclusion periods (HR: 1.71; 95% CI: 1.07–2.30, HR: 1.70; 95% CI: 1.05–2.49, and HR: 1.71; 95% CI: 1.01-2.52). High waist circumference was strongly associated with CVD mortality after exclusion of the first 2, 5, and 10 years (HR: 4.76; 95% CI: 1.70–11.82, HR: 4.75; 95% CI: 1.56–11.88, and HR: 4.73; 95% CI: 1.42–12.90, respectively). Elevated waist-to-hip ratio similarly showed associations with CVD mortality (HR: 2.69; 95% CI: 1.10–5.60, HR: 2.66; 95% CI: 1.12–5.75, and HR: 2.64; 95% CI: 1.03–7.32). Body mass index, waist circumference, waist-to-height ratio, and waist-hip ratio were not associated with respiratory and cancer mortality. Conclusions: Waist circumference was the adiposity marker most strongly associated with all-cause and CVD mortality, even after excluding the first 10 years of follow-up. © The Author(s), under exclusive licence to Springer Nature Limited 2025.